PROBLEMS OF CONTENT PRODUCTION IN REGIONAL MASS MEDIA - Murinska, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This article examines problems and importance of content production in regional information space. This is an emerging question within a rapidly restructuring media landscape, and globalized information flows with aim to manipulate and destroy democratic order. Policy guidelines for Latvian media 2016 – 2020 describes five steps how to fight against these hazards. One of the steps are the strengthening of local information area and facilitating media pluralism, many tasks are dedicate to support regional media, realizing media fund programs with aim to ensure the availability of information for people in the regions. Regional journalism is classified as unexplored field of research, especially in Latvia, there is a lack of researches about how local journalism should work and what are their working strategies and problems. This article analysis data of survey made among local journalists about their content production practices. The aim was to explore a) what are criteria for content production and selection of news, b) what kind of information is making local information space, c) what are the threats for journalism in regions. Respondents were local journalists in Latgale region of Latvia working in local newspapers, radio and television.Results encountered a very strong attachment to local community and identity construction not to so much dealing with journalistic mission and techniques.